Concurrent Placements of a Duodenal-Jejunal Bypass Liner and an Intragastric Balloon Among Severely Obese Patients: A Case Series. Issue 6 (June 2019) - Sartoretto, Adrian; Marinos, George; Sui, Zhixian
Abstract : ABSTRACT: The duodenal-jejunal bypass liner and the intragastric balloon are endoscopically deployed devices used in the treatment of obesity and diabetes. These devices use differing mechanisms of action, and concurrent use may lead to improved efficacy. Three obese patients who suffered from weight loss plateau with the liner had the intragastric balloon inserted concurrently. All 3 patients reported subsequent significant weight loss. None of the patients reported any symptom that indicate the interference between the devices. This is the first case series in humans of successfully combining 2 independent endoscopic bariatric therapies to overcome weight loss plateau in the primary treatment of obesity.